DAMPAK PASTORAL SEKOLAH BAGI PERKEMBANGAN IMAN REMAJA SMPK DI KOTA MADIUN - Rosmini, Natalia; Supriyadi, Agustinus (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2020)
Pastoral school is a pastoral care, mentoring and faith formation activity for students in Catholic schools. In this mentoring and faith formation, the pastoral school organizes various activities such as religious lessons, catechesis, liturgical activities, deepening of the faith, recollections, retreats, pilgrimages, visits to orphanages, fasting, and group recreation. This research uses qualitative methods. This research was conducted from April 21 to May 5 2020. The total number of respondents was 7 people, with details of 4 respondents from St. Yusuf and 3 respondents from St. Bernadus Junior High School, who is actively involved in pastoral development activities in their respective schools. The results of the research showed that all respondents (100%) were able to explain the meaning of pastoral school as a place for cultivating children's faith in the school environment. All respondents (100%) provided an understanding regarding the importance of developing children's faith through pastoral activities. Regarding the impact of pastoral school on the development of children's faith in Junior High School, the majority of respondents (85.71%) could see the positive impact of pastoral activities on the development of children's faith. However, one respondent (14.28%) stated that pastoral school care had a less significant impact because there were still many children who did not want to be involved in spiritual activities.